A questão da qualificação profissional diante dos impactos da reestruturação produtiva: análise de um curso de engenharia de alimentos da cidade de Uberaba - Fugeiro, Márcia Beatriz Velludo Araújo (2007)
This research is based on the premise that the contemporary capitalism has brought to surface questions which have directly impacted the men s life, mainly in respect of education and work. It considers that the reorganization in production means has provoked significant unfoldings especially in issues concerned with work and in the qualifications required to perform it. It is used the following categories for analysis: education, qualification, work and productive reorganization. In order to understand the concepts of work, qualification, abilities as well as the changes that are inherent to the inconstancy present in the working environment and in the market, which dictate the rules for life in society, we have used the bibliographical research. We analyze the college Pedagogical Project chosen for the empirical research, elaborated according to the curricular lines of direction established by the certified agencies. The questions that guided the analysis of the Pedagogical Project and the representation of former pupils of the course and the interviewed coordinators were: how do professors, former pupils and coordinator of this course see and perceive the impact of such issues in the working environment? To what extent do the syllabus enables an adequate professional practice? How do these segments understand their formation from prospect of a system of abilities? The analyses were made under the theoretic- conceptual matrices of this system, establishing comparisons between the analyzed document and the research done through a questionnaire. Finally, we ponder on what type of society we intend to live, which ideal standards we can expect from school, and of the market, for promoting social equality and autonomy, both of which responsible for generating man s emancipation. The main results of the research showed that both in the level of educational politics for courses of superior education, materialized by means of the National Curricular Lines of direction, and according to the proposals evidenced in the Pedagogical Project, there is inadequate use of the terms ability and qualification, thus narrowing the formation of the professionals of the course analyzed. On the other hand, we also verified that the concepts of qualification, ability and professional formation have many different connotations and, therefore, are generally used in an inadequate way in literature.